2020
DOI: 10.1080/00405000.2020.1805971
|View full text |Cite|
|
Sign up to set email alerts
|

From containment to harm reduction from SARS-CoV-2: a fabric mask for enhanced effectiveness, comfort, and compliance

Abstract: Although the COVID-19 pandemic shows no signs of abating, public health strategies have transitioned from containment to harm reduction. In light of this paradigm shift, it is critical that individuals take steps to prevent the spread of SARS-CoV-2, the virus that causes COVID-19. In the United States, the CDC recommends that individuals wear face coverings in public places, such as grocery stores. As lockdowns are being phased out around the world, authorities are requiring the use of such masks in public pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…However, the moist environment of a face mask and the known rapid dissolution of AgNPs to Ag 45 suggests that the total Ag measurement in this study is representative of the most toxic potential silver exposure possible as the metals are in a dissolved form. These conditions are representative of what many essential workers endure, including preparing food in hot kitchen, waiting tables, working construction, and hauling goods, where it is likely for masks to become saturated over the course of a workday 46 . Studies have shown that in humid environments, or when worn for long periods of time, masks quickly become saturated 47 with saliva droplets 48 , 49 that are expelled during talking, sneezing, or coughing 50 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the moist environment of a face mask and the known rapid dissolution of AgNPs to Ag 45 suggests that the total Ag measurement in this study is representative of the most toxic potential silver exposure possible as the metals are in a dissolved form. These conditions are representative of what many essential workers endure, including preparing food in hot kitchen, waiting tables, working construction, and hauling goods, where it is likely for masks to become saturated over the course of a workday 46 . Studies have shown that in humid environments, or when worn for long periods of time, masks quickly become saturated 47 with saliva droplets 48 , 49 that are expelled during talking, sneezing, or coughing 50 .…”
Section: Resultsmentioning
confidence: 99%
“…The flat-fold mask was the most comfortable because of the light material, whereas the surgical mask with the bandage caused the most difficult breathing because of the thick material. Park and Jayaraman (2020) in the United States studied mask designs based on required performances, such as being breathable and comfortable using the quality function deployment method. Lee et al (2020) in China explored finding the comfortability factor for reusable cloth masks by measuring thermal conductivity, air permeability and water vapor permeability.…”
Section: Discussionmentioning
confidence: 99%
“… 52 Higher pressure drop associated with face mask alleviates suffocation and hence not desirable. 53 Hence, such a study may serve to establish the effectiveness of double masking from both filtration and breathability/comfort perspectives.…”
Section: Methodsmentioning
confidence: 99%